(untitled) (Scientific journal of the Fergana State University, 2025)
In the first half of the last century, a dismissive attitude towards past culture increased. Despite this, Russian and our local intellectuals established organizations to preserve the cultural heritage monuments in our region. These organizations paid great attention to studying the monuments, compiling their lists, and carrying out restoration work. It should be noted that one of the most active publications in this field was the journal "Education and Teacher", which, in the 1920s–1930s, served as the publishing organ of the People’s Commissariat of Education of the Uzbek SSR. The journal was publishing research by national intellectuals in history, literary studies, ethnology, archaeology, and other fields. This article analyzes the intellectuals’ attitude towards historical and cultural heritage.